Placement Tests The Writer's Reactions - Kizza, Immaculate ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
A study examined students' reactions to a writing placement test. Subjects, 98 fall 1992 freshmen at the University of Tennessee Chattanooga, completed a questionnaire. Results indicated that: (1) only 24% liked the assigned writing topic; (2) 97% found the statement of the topic clear and understandable; (3) 77% were comfortable with the one hour allowed for the test; (4) 85% found the room comfortable; (5) 75% felt prepared for the test, but in different ways; and (6) 76% indicated that they could "hold their own" as writers. Follow-ups indicated that 98% of the students successfully completed whichever course they were placed in based on the placement test. Recommendations include: setting familiar topics that transcend socioeconomic barriers, previous preparation, and experience; and bridging the gap between high school English teachers and their college counterparts so that they can discuss their expectations of and assumptions about student writing. (RS)
ERIC Note: Paper presented at the Annual Meeting of the Conference on College Composition and Communication (44th, San Diego, CA, March 31-April 3, 1993).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Freshmen; Freshman Composition; Higher Education; Student Attitudes; Student Placement; Writing Attitudes; Writing Research; Writing Tests; University of Tennessee Chattanooga; Speeches/Meeting Papers; Reports, Research